(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2019)
This work, we analyze the legitimated assets and liabilities in the scope of the Federal Special Court, considering that the legitimacy defines the competence in reason of the person. Article 6 of Law 10.259/01 brings the role of the legitimized, however, there are several doubts about the existence of others legitimized. The analysis, it is concluded that the role of legitimates is greater than those listed in Article 6, and that the limitation of jurisdiction on the basis of the person does not violate the principle of procedural equality, but allows to exercise a jurisdiction differentiated, effective, with simplified process.